Measurement and modeling of real impedance results in dependence on the position the sensing electrodes - Haňka, J. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Content of this work is aimed to solutions of issues created due experimental measurement impedance properties of dielectric materials by sensitive impedance spectroscopy analysis. To this purpose should be created mathematical model by suitable simulation software, which should be able to simulate impedance changes in dependence of electrodes position. The work deals with description of complex impedance system behavior and response to electrodes position changes.
Keywords: Impedance spectroscopy; Ansys; Electroceramics